A Questionnaire for the Assessment of Pragmatic Competence in Children Aged 5-8 - E.S. Oshchepkova; N.A. Kartushina; K.S. Tarasova (Клиническая и специальная психология)
The work aims to test a new questionnaire for parents and educators to assess the pragmatic competence of children from 5 to 8 years old. Parents of 753 children and teachers of 903 children from preschool institutions took part in the testing, filling out the proposed questionnaire online. Subsequently, after the initial analysis, 674 parent questionnaires remained in the work, of which 287 questionnaires were from parents of five-year-old children (130 of them boys), 213 from parents of six-year-old children (108 boys), 131 from parents of seven-year-old children (60 boys) and 43 from parents of eight-year-old children (21 boys). And also 903 questionnaires of preschool teachers (at this stage we did not include a survey of school teachers): 487 children of 5 years old (214 boys), 409 children of 6 years old (206 boys) and 7 children of 7 years old (4 boys). Statistical analysis of the material included: 1) checking for normality of the distribution of answers; 2) analysis for consistency of the entire questionnaire, its scales and individual questions; 3) exploratory factor analysis; 4) confirmatory factor analysis; 5) identifying gender differences for each of the questions using the Mann-Whitney test. The study showed that the pragmatic competence of children includes: 1) understanding of the literal and figurative meaning of statements; 2) mastery of non-verbal means of communication; 3) communication skills: politeness, openness to communication, adequate response to the expectations of the interlocutor; 4) development of verbal creativity in various genres, including fantasy. The results of the analysis showed that girls’ pragmatic competence at the age of 5-8 years was better developed than boys, however, in general, in normatively developing children by the age of 5, the main aspects of pragmatic competence have already been developed, and in the future may deteriorate, but understanding the figurative meaning of statements continues to develop at school. This questionnaire requires some refinement and testing for test-retest and external validity.